Real-World Outcomes with Chimeric Antigen Receptor T Cell Therapies in Large B Cell Lymphoma: A Systematic Review and Meta-Analysis - Jacobson, Caron A.; Munoz, Javier; Sun, Fang; Kanters, Steve; Limbrick-Oldfield, Eve H.; Spooner, Clare; Mignone, Krystal; Ayuk, Francis; Sanderson, Robin; Whitmore, James; Wang, Yuanyuan; Xu, Hairong; et al. (Transplantation and cellular therapy, 2024)
•A rich body of real-world evidence has been developed for chimeric antigen receptor T cell (CAR-T) therapies in LBCL.•In the real world, CAR-T was used in a broader patient population than in trials.•Real-world CAR-T effectiveness and safety were comparable with trial results.•Axi-cel was associated with better effectiveness compared with tisa-cel.•Tisa-cel was associated with a lower risk of neurologic events compared with axi-cel. Chimeric antigen receptor T cell (CAR-T) therapies, including axicabtagene ciloleucel (axi-cel) and tisagenlecleucel (tisa-cel), are innovative treatments for patients with relapsed or refractory (r/r) large B cell lymphoma (LBCL). Following initial regulatory approvals, real-world evidence (RWE) of clinical outcomes with these therapies has been accumulating rapidly. Notably, several large registry studies have been published recently. Here we comprehensively describe clinical outcomes with approved CAR-T therapies in patients with r/r LBCL using available RWE. We systematically searched Embase, MEDLINE, and 15 conference proceedings to identify studies published between 2017 and July 2022 that included ≥10 patients with r/r LBCL treated with commercially available CAR-T therapies. Eligible study designs were retrospective or prospective observational studies. Key outcomes of interest were objective response rate (ORR), complete response (CR) rate, overall survival (OS), progression-free survival (PFS), cytokine release syndrome (CRS), and immune effector cell–associated neurotoxicity syndrome (ICANS). Random-effects meta-analyses were used to compare real-world outcomes with those of pivotal clinical trials and to compare clinical outcomes associated with axi-cel and tisa-cel. Study cohort mapping was conducted to avoid including patients more than once. Of 76 cohorts we identified, 46 reported patients treated specifically with either axi-cel or tisa-cel, with 39 cohorts (n = 2754 patients) including axi-cel and 20 (n = 1649) including tisa-cel. No studies of liso-cel that met the inclusion criteria were identified during the search period. One-half of the tisa-cel cohorts were European, compared with 33% of the axi-cel cohorts. Among studies with available data, axi-cel had a significantly shorter median time from apheresis to CAR-T infusion than tisa-cel. Despite including broader patient populations, real-world effectiveness and safety of both axi-cel and tisa-cel were consistent with data from the pivotal clinical trials. Comparative meta-analysis of axi-cel versus tisa-cel demonstrated adjusted hazard ratios for OS and PFS of .60 (95% confidence interval [CI], .47 to .77) and .67 (95% CI, .57 to .78), respectively, both in favor of axi-cel. Odds ratios (ORs) for ORR and CR rate, both favoring axi-cel over tisa-cel, were 2.05 (95% CI, 1.76 to 2.40) and 1.70 (95% CI, 1.46 to 1.96), respectively. The probability of grade ≥3 CRS was comparable with axi-cel and tisa-cel, whereas axi-cel was associated with a higher incidence of grade ≥3 ICANS (OR, 3.95; 95% CI, 3.05 to 5.11). Our meta-analysis indicates that CAR-T therapies have manageable safety profiles and are effective in a wide range of patients with r/r LBCL, and that axi-cel is associated with improved OS and PFS and increased risk of grade ≥3 ICANS compared with tisa-cel. Limitations of this study include nonrandomized treatments, potential unknown prognostic factors, and the lack of available real-world data for liso-cel.